VN/S Nanoclusters Encapsulated with Graphene via Zeta Potential Control: A Pomegranate‐Like Cathode for Lithium‐Sulfur Batteries with Enhanced Rate Performance. Issue 7 (6th April 2020) - Qu, Long; Liu, Pei; Tian, Xiaolu; Shu, Chengyong; Yi, Yikun; Yang, Pu; Wang, Te; Fang, Binren; Li, Mingtao; Yang, Bolun
Abstract: A pomegranate‐like cathode, VN/S@G, is synthesized according to a simple principle of electrostatic attraction through a controllable Zeta potential method, establishing a hierarchical‐structured VN/S nanoclusters encapsuled with graphene nanosheets. Internal VN nanoparticles trap lithium polysulphides (LiPSs) and catalyse them transforming from long‐chain to short‐chain species; whereas the external cladding layers of graphene nanosheets confine the transformations in a nanoscale‐catalysis reactors. VN/S@G cathode exhibits excellent long‐cycling life at 2 C rate during the 2000 cycles, corresponding to 0.038 percent of capacity fade per cycle. According to in‐situ Raman and electrochemical impedance spectroscopies, VN catalyst accelerates chemical transformations of liquid‐state LiPSs to solid‐state Li2 S2 /Li2 S and graphene intensifies Li + diffusion behaviour. Improvement of electrochemical performance of the VN/S@G cathode depends on a coefficient of physical and chemical interactions between VN catalyst and LiPSs species. Abstract : Inside and out : A novel cathode is synthesized by controlling the Zeta potential to establish a pomegranate‐like VN/S@G. The interior of the VN catalyst traps LiPSs and catalyzes them transforming from long‐chain to short‐chain species; whereas the external cladding layers of graphene nanosheets confine the transformations in nanoscale spaces. The cathode exhibits ultralong‐cycling life, with a 0.038 percent of capacity fade per cycle at 2 C rate within 2000 cycles.